Pharmacology of levosimendan: inotropic, vasodilatory and cardioprotective effects. (18th April 2013) - Pathak, A.; Lebrin, M.; Vaccaro, A.; Senard, J. M.; Despas, F.
Summary: What is known and objective: Positive inotropic agents are frequently used in acute decompensated heart failure (ADHF) due to left ventricular systolic dysfunction. These agents are known to improve cardiac performance and peripheral perfusion in the short‐term treatment. However, several preclinical and clinical studies emphasized detrimental effects of these drugs on myocardial oxygen demand and on sympathetic tone entailing arrhythmogenesis. Levosimendan is an inotropic agent with an original mechanism of action. This review focuses on major data available for levosimendan. Methods: A literature search was conducted in the PubMed database by including studies published in English using combinations of the following key words, levosimendan, inotropic drugs and acute heart failure . Furthermore, bibliographies of selected references were also evaluated for relevant articles. The collection for this review was limited to the most recently available human and animal data. Results and discussion: Levosimendan's vasodilatory and cardioprotective effects are mediated by calcium sensitization of contractile proteins and opening of adenosine triphosphate (ATP)‐dependent K+ channels in vascular smooth muscle cells and on mitochondrial ATP‐sensitive potassium [mito.K(ATP)] channels. This inotropic agent has mild PDE inhibitory action. Unlike other inotropic agents, levosimendan improves cardiac performance without activating the sympathetic nervous system. Moreover, there are evidences that levosimendan has additional anti‐inflammatory and anti‐apoptotic properties that prevent cardiac toxicity and contributes to positive hemodynamic response of the drug. Four randomized trials evaluated the effects of levosimendan on mortality in patients with acute decompensated chronic heart failure; nevertheless, a clear benefit has not been demonstrated so far. Although levosimendan is indicated for the treatment of ADHF (class of recommendation IIa, level of evidence B), it is has not been approved in all countries. What is new and conclusion: This review summarizes the characteristics and the current knowledge of the literature on levosimendan and its active metabolite OR‐1896.